2018
DOI: 10.1001/jamapsychiatry.2018.1867
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Peer Comparison Letters for High-Volume Primary Care Prescribers of Quetiapine in Older and Disabled Adults

Abstract: ClinicalTrials.gov identifier: NCT02467933.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
107
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(117 citation statements)
references
References 30 publications
5
107
3
1
Order By: Relevance
“…We feel that, beyond educational interventions, the peer pressure generated by the continuous open benchmarking played a determinant role in the success of our strategy. 33 The direct laboratory costs showed a significant growth reduction (secondary outcome); we have however to acknowledge that we have only stopped the growing in the request of tests and that we are probably still far away from a reasonable baseline.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…We feel that, beyond educational interventions, the peer pressure generated by the continuous open benchmarking played a determinant role in the success of our strategy. 33 The direct laboratory costs showed a significant growth reduction (secondary outcome); we have however to acknowledge that we have only stopped the growing in the request of tests and that we are probably still far away from a reasonable baseline.…”
Section: Discussionmentioning
confidence: 90%
“…The implementation of a centralised web‐based system, accessible to every health care provider involved in the care of the hospitalised patients, delivering unmasked data, called “Reporting Wisely,” yielded substantial reductions in the number of lab tests and volume of blood withdrawals per patient (primary and secondary outcome, respectively). We feel that, beyond educational interventions, the peer pressure generated by the continuous open benchmarking played a determinant role in the success of our strategy . The direct laboratory costs showed a significant growth reduction (secondary outcome); we have however to acknowledge that we have only stopped the growing in the request of tests and that we are probably still far away from a reasonable baseline.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, peer benchmarking also substantially changed physician behavior in a cohort of physicians who received peer comparison letters about their high-volume prescribing frequency of quetiapine in older patients. 37 Finally, in a study at our institution, we observed a reduction in unnecessary blood transfusions among surgeons who were given a transfusion report accounting for case type, complexity, and comorbidity relative to peers 34 and are now applying the model in a national collaborative to reduce opioid overprescribing in narcotic-naive patients after standardized procedures. 38 These studies demonstrate that physicians with outlier practice patterns can be identified using claims data and that individual physician-level feedback can have an impact on the problem of lowvalue and unnecessary care.…”
Section: Discussionmentioning
confidence: 90%
“…27 Both the content and author/sender of the memo in this study were likely also key to the intervention's success. 28 In this case, the emailed memo was signed/sent by the CEO of the physicians' clinically integrated network and endorsed by the leadership of the health system's primary care group. Indeed, behavioral literature suggests that authority of the writer gives the Figure 3.…”
Section: Discussionmentioning
confidence: 99%